2008
DOI: 10.1524/zpch.2008.5359
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Dipolar Ortho/Para-H2O Conversion in Ice

Abstract: In this paper a possible explanation for an unexpected ortho/para-water ratio in the gas clouds of comets is given. The description is based on the quantum-mechanical density matrix formalism and the spin temperature concept. Only the nuclear spin system is treated quantum-mechanically. Employing the model of a four spin system, created by two nearest neighbour water molecules, spin eigenstates and their dynamics under the influence of their mutual dipolar interactions are studied. It is shown that a fast conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 45 publications
(50 reference statements)
1
57
0
1
Order By: Relevance
“…Theoretical calculations of Buntkowsky et al (2008) show that this happens in an ice matrix even on timescales of milliseconds. Recent experiments (Hama et al 2011) suggest that the o/p ratio of thermally desorbed water -originally deposited at 8 K -is always close to three, which is the high temperature limit.…”
Section: The Water O/p Line Ratiosmentioning
confidence: 99%
“…Theoretical calculations of Buntkowsky et al (2008) show that this happens in an ice matrix even on timescales of milliseconds. Recent experiments (Hama et al 2011) suggest that the o/p ratio of thermally desorbed water -originally deposited at 8 K -is always close to three, which is the high temperature limit.…”
Section: The Water O/p Line Ratiosmentioning
confidence: 99%
“…Buntkowsky et al (2008) have studied the case of two water molecules from a theoretical point of view. They have shown that the frustration of the rotation reduces considerably the difference in energy of the rotational levels.…”
Section: Nuclear Spin Conversion On Cold Surfacesmentioning
confidence: 99%
“…I will present some results obtained in noble gas matrix that demonstrate the dependence of the NSC on the concentration of H 2 O, suggesting that the NSC is accelerated with water-water interaction. I will recall the theoretical results obtained by Buntkowsky et al (2008), that show that the interaction of 2 water molecules should produce NSC in the millisecond timescale. I will finally discuss the possibility that selective desorption of water in function of the spin isomer can produce a disequilibrium in the opr of the nascent molecules detected in the gas phase.…”
mentioning
confidence: 96%
“…However, unlike other small polyatomic molecules exhibiting spin isomerism, such as fluoromethane or ethylene [15,16] , which were spin-isomerically enriched using the light induced drift technique [7] , this has not been achieved for water. Separation through selective adsorption on surfaces was reported [17] , but these results remain controversial and could not be reproduced [18][19][20][21] . Thus, studies of spin-conversion dynamics in water have been limited to water embedded in rare gas matrices, with relative spin populations modified by the sample temperature [22] .…”
mentioning
confidence: 99%